PEMODELAN PERUBAHAN IKLIM DAERAH KABUPATEN TUBAN MENGGUNAKAN MAGICC/SCENGEN - Marita Ika Joesidawati (Agriekonomika, 2012)
ABSTRAKModeling of climate change requires heavy and complicated computing; it is not surprising that early development is limited just for a few institutions. One of climate scenario device of MAGICC/SCENGEN is widely used. This study aims to determine the rate of Indonesia climate change (temperature and precipitation) with the MAGICC model simulations-SCENGEN (global circulation models CCSR / NIES Japan, and the CSIRO Australia) with the scenarios A2 and B2-AIM-AIM. Global average temperature change based on A2-AIM and B2 AIM increase linearly.  Both scenarios on different focus and same region show different rate. This confirms the increase of the average temperature for the future and Tuban shows different and irregular patterns. In general, the model projected increase in precipitation is quite high in the wet months (December to February) and the transitional months between seasons (March-May and September-November) but precipitation changes is decreases in the dry months. Modeling results indicates precipitation tends to increase in wet month.Keywords:Climate change, MAGICC/SCENGEN.